2017
DOI: 10.56059/jl4d.v4i1.154
|View full text |Cite
|
Sign up to set email alerts
|

Distance Learner’s Perspective on User-friendly Instructional Materials at the University of Zambia

Abstract: This case study focuses on print-based instructional materials available to distance education learners at the University of Zambia. Using the Visual Paradigm Software, we model distance education learners’ voices into sociograms to make a contribution to the ongoing discourse on quality distance learning in lowly resourced communities. The key finding shows that out of the four modules (PEM 2082, PEM 2061, PEM 2071, PEM 3122) engaged in, learners rated PEM 2082 as the most user-friendly module at 65.9% while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…The result also confirmed the assertion of Simui et al, et al (2017) that one of the features that enable instructional material identified are to become user-friendly, the use of illustrations, design and layout within the learning units.…”
Section: Significant Relationship Between the Components And Format O...supporting
confidence: 77%
“…The result also confirmed the assertion of Simui et al, et al (2017) that one of the features that enable instructional material identified are to become user-friendly, the use of illustrations, design and layout within the learning units.…”
Section: Significant Relationship Between the Components And Format O...supporting
confidence: 77%
“…Socially through gaining friends and academically as a strategy for teaching as used by some or most teachers. In the study conducted by Simui et al (2017), they enumerated the key elements that an instructional designer needs to consider including presentation and layout of content, inclusion of real-life situations, and use of interactive language. These elements were considered in designing the learning material used in this study, thus students find it user-friendly.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Addressing this funding gap is essential for fostering a robust and equitable education system that empowers all students for the challenges of the future. Simui, et al (2017) reported that the funding of schools for teaching and learning materials is the back bone of every effective education in way beyond imagination. The inadequacy funding to schools poses a lot of hardships in delivering the appropriate curriculum to the young learners.…”
Section: Statement Of the Problemmentioning
confidence: 99%